Green Synthesis of Silver Nanoparticles Using Euphorbia Microsphaera: Tuning Size and Stability Via Precursor Concentration - Hasan, Ahmed Qays; Abdul Hassan, Duha Abdul Sahib (Scripta Medica, 2026)
Background/Aim: The green synthesis of silver nanoparticles (AgNPs) by plant extracts provides an environmentally friendly alternative to traditional chemical methods. This study aimed to report the biosynthesis of AgNPs using Euphorbia microsphaera, a native plant of the Middle East and to investigate how different precursor concentrations affect the physicochemical properties of the synthesised nanoparticles. Methods: The methanolic extracts prepared from E microsphaera leaves were employed for the fabrication of AgNPs at varying precursor concentrations such as 1, 3 and 5 mM in silver nitrate (AgNO3). The formation of NPs was observed visually and by measurement with UV-VIS spectroscopy. Dynamic light scattering (DLS) was used to determine the hydrodynamic size, polydispersity index (PDI) and zeta potential. Morphological and elemental analyses were conducted by utilising scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDS). Results: A clear colour change from pale yellow to dark crimson pink suggested a successful biosynthesis of AgNPs. UV-Vis spectroscopic analysis showed a distinct surface plasmon resonance (SPR) peak at 452.5 nm for the 1 mM sample, indicating the formation of small, monodispersed nanoparticles. In contrast, at 5 mM, a pronounced red shift to 530.5 nm was observed, accompanied by a substantial increase in hydrodynamic size from 238.8 nm to more than 2000 nm. TEM and SEM images supported the results obtained from UV–vis, depicts a well-dispersed spherical shaped nanoparticles in size range 20–50 nm at concentration of 1 mM, whereas 5 mM showed massive agglomeration associated to the saturation of the capping agent. Conclusion: This study successfully showed the green synthesis of AgNPs by using E microsphaera. The results revealed the significant effect of precursor concentration on nanoparticle stability and 1 mM was found to be the optimal value for high stability of monodisperse nanoparticles. E microsphaera can be considered as a promising bio-resource for nanotechnology in the biomedicine area.